Neonatal mortality, risk factors and causes: a prospective population-based cohort study in urban Pakistan - Imtiaz Jehan; Hillary Harris; Sohail Salat; Amna Zeb; Naushaba Mobeen; Omrana Pasha; Elizabeth M McClure; Janet Moore; Linda L Wright; Robert L Goldenberg (The World Health Organization, 2009)
OBJECTIVE: To evaluate the prevalence, sex distribution and causes of neonatal mortality, as well as its risk factors, in an urban Pakistani population with access to obstetric and neonatal care. METHODS: Study area women were enrolled at 20-26 weeks' gestation in a prospective population-based cohort study that was conducted from 2003 to 2005. Physical examinations, antenatal laboratory tests and anthropometric measures were performed, and gestational age was determined by ultrasound to confirm eligibility. Demographic and health data were also collected on pretested study forms by trained female research staff. The women and neonates were seen again within 48 hours postpartum and at day 28 after the birth. All neonatal deaths were reviewed using the Pattinson et al. system to assign obstetric and final causes of death; the circumstances of the death were determined by asking the mother or family and by reviewing hospital records. Frequencies and rates were calculated, and 95% confidence intervals were determined for mortality rates. Relative risks were calculated to evaluate the associations between potential risk factors and neonatal death. Logistic regression models were used to compute adjusted odds ratios. FINDINGS: Birth outcomes were ascertained for 1280 (94%) of the 1369 women enrolled. The 28-day neonatal mortality rate was 47.3 per 1000 live births. Preterm birth, Caesarean section and intrapartum complications were associated with neonatal death. Some 45% of the deaths occurred within 48 hours and 73% within the first week. The primary obstetric causes of death were preterm labour (34%) and intrapartum asphyxia (21%). Final causes were classified as immaturity-related (26%), birth asphyxia or hypoxia (26%) and infection (23%). Neither delivery in a health facility nor by health professionals was associated with fewer neonatal deaths. The Caesarean section rate was 19%. Almost all (88%) neonates who died received treatment and 75% died in the hospital. CONCLUSION: In an urban population with good access to professional care, we found a high neonatal mortality rate, often due to preventable conditions. These results suggest that, to decrease neonatal mortality, improved health service quality is crucial.